Philosophic and Ethic Bases of Spiritual-Moral Education of Children in the History of Ukraine - Viktoriya Vorozhbit (Pedagogical Discourse, 2013)
The author revealed the philosophical and ethic foundations of spiritual and moral education of children in the history of Ukraine in the XV–XVII centuries. The article states that Orthodox patriarchal approach to education in the Ukrainian lands remained at that time, but the coordination with social position was quite expressive. Spiritual and moral education of children in the family and in schools provided for the following of the rigid canons. Educational process in the Cossack brotherhood was realized with clear requirements. Among the traditional forms of spiritual and moral education there was the blessed ordinance, the sacrament of confession and edification in the Christian law implementation. Also there was the observance of the chivalry code, donations, physical and moral hardening.